2005
DOI: 10.1007/s00441-004-1029-9
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol protects cultured articular chondrocytes from oxygen-radical-induced damage

Abstract: Osteoarthritis (OA) is aggravated in menopausal women possibly because of changed serum estrogen levels. Estradiol has been postulated to affect oxidative stress induced by reactive oxygen species (ROS) in articular chondrocytes. We generated ROS in cultured bovine articular chondrocytes by incubating them with combined Fe2SO4, vitamin C, and hydrogen peroxide. The release of thiobarbituric-acid-reactive substances (TBARS, lipid peroxidation) and lactate dehydrogenase (LDH, membrane damage) was measured photom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 37 publications
3
41
0
2
Order By: Relevance
“…Interestingly, application of 17-h-estradiol in male guinea pigs decreased, while tamoxifen in female guinea pigs increased concentration of the heart form of LDH (H-LDH). Suppression of LDH production by estrogen has already been demonstrated [17,18]. Taken together, our data indicate that estrogen modulates the effects of pinacidil specifically, and additionally downregulates production of H-LDH.…”
Section: Discussionsupporting
confidence: 64%
“…Interestingly, application of 17-h-estradiol in male guinea pigs decreased, while tamoxifen in female guinea pigs increased concentration of the heart form of LDH (H-LDH). Suppression of LDH production by estrogen has already been demonstrated [17,18]. Taken together, our data indicate that estrogen modulates the effects of pinacidil specifically, and additionally downregulates production of H-LDH.…”
Section: Discussionsupporting
confidence: 64%
“…Recently, we have shown that 17β-estradiol possesses antioxidative properties and prevents membrane damage of bovine articular chondrocytes monitored by LDH release (Claassen et al 2005). Since the effects of daidzein and genistein reported here differ from those of 17β-estradiol, antioxidative mechanisms stabilizing the plasmatic membrane are probably not involved.…”
Section: Immunocytochemical Characterizationmentioning
confidence: 91%
“…This confers estrogen the property of an antioxidant. In this regard, estrogen has been shown to protect various cell types during acute stress by increasing the anti-oxidant properties of the cells (57,58). Further, Wiseman (59) found that the administration of estrogen inhibited lipid peroxidation in microsomal and liposomal systems.…”
Section: Accepted Manuscriptmentioning
confidence: 96%